Peran Pendidikan Dan Pelatihan, Kegiatan Non Diklat, Promosi Dan Motivasi Terhadap Kinerja Pegawai Pada UPTD KPH UNIT XXIV Gularaya Dinas Kehutanan Provinsi Sulawesi Tenggara - Dharma Prayudi; Nursaban Rommy; Sudirman Zaid (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to determine the effect; 1) The effect of education and training on employee performance. 2) The influence of non-education and training activities on employee performance. 3) The effect of promotion on employee performance and 4) The influence of technology motivation on employee performance. The research method is to use quantitative research. The data used are secondary and primary data. Data analysis usingSPSS software version 20. The sampling technique uses saturated sample amounted to 50 employees at UPTD KPH UNIT XXIV Gularaya Forestry Service of Southeast Sulawesi Province. The results showed that; 1) education and training have a positive and significant effect on employee performance. 2) non-education and training activities have a positive and significant effect on employee performance. 3) promotion has a positive and significant effect on employee performance. 4) motivation has a positive and significant effect on employee performance.